Reevaluating the Concept of Treating Experimental Tumors with a Mixed Bacterial Vaccine: Coley’s Toxin - C. Maletzki; U. Klier; W. Obst; B. Kreikemeyer; M. Linnebacher (Clinical and Developmental Immunology)
Several decades after Coley’s initial work, we here systematically analyzed tumoricidal as well as immunostimulatory effects of the historical preparation Coley’s Toxin (CT), a safe vaccine made of heat-inactivated S. pyogenes and S. marcescens. First, by performing in vitro analysis, established human pancreatic carcinoma cell lines responded with dose- and time-dependent growth inhibition. Effects were attributed to necrotic as well as apoptotic cell death as determined by increased Caspase 3/7 levels, raised numbers of cells with sub-G1-DNA, and induced p expression, indicative for cell cycle arrest. Besides, CT effectively stimulated human peripheral blood leukocytes (huPBL) from healthy volunteers. Quantitative gene expression analysis revealed upregulated mRNA levels of selected Toll-like receptors. Flow cytometric phenotyping of CT-stimulated huPBLs identified raised numbers of CD25+-activated leukocytes. In vivo, repetitive, local CT application was well tolerated by animals and induced considerable delay of Panc02 tumors. However, systemic treatment failed to affect tumor growth. Antitumoral effects following local therapy were primarily accompanied by stimulation of innate immune mechanisms. Data presented herein prove that the historical approach of using killed bacteria as active immunotherapeutic agents still holds promise, and further careful preclinical analyses may pave the way back into clinical applications.